Hubungan Proses Belajar Daring Masa Pandemi Covid-19 Dengan Prestasi Belajar IPA Siswa Kelas X SMA Negeri 2 Tondano - Syahriyani Timin; Sanusi Gugule; Anderson Aloanis (Oxygenius Journal Of Chemistry Education, 2022)
This study aims to determine the relationship between the online learning process during the Covid-19 pandemic and the science learning achievement of class X SMA Negeri 2 Tondano students. The online learning process is a teaching and learning process that is carried out online and interactively by utilizing information and communication technology, such as computer media with the internet as the delivery and recipient of the material. The research design used is correlational, with data collection techniques in the form of questions (statements) questionnaires and the average value of report cards using 20 students as samples. Tests carried out to prove the hypothesis were carried out by simple linear regression analysis, Pearson Product Moment correlation and t-test. The results of the regression equation obtained are Y = 0.2634x + 68.519 with a correlation value of r = 0.693 in the level of strong relationship, and the results from the t-test are tcount = 4.080 and ttable = 2.100, meaning tcount > ttable at = 0,05, the correlation between variables X and Y is significant, meaning that there is a strong and significant relationship between the online learning process during the Covid-19 pandemic and the science learning achievement of class X SMA Negeri 2 Tondano students.